2018
DOI: 10.1016/j.ssmph.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A smart-phone intervention to address mental health stigma in the construction industry: A two-arm randomised controlled trial

Abstract: BackgroundHigh levels of self-stigma are associated with a range of adverse mental health, treatment, and functional outcomes. This prospective study examined the effects of an electronic mental health stigma reduction intervention on self-stigma (self-blame, shame, and help-seeking inhibition) among male construction workers in Australia.MethodMale construction workers (N = 682) were randomly assigned to receive either the intervention condition or the wait list control over a six-week period. Self-stigma was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
0
44
0
1
Order By: Relevance
“…Contrary to our hypothesis and previous findings (Alderson, 2017), construction workers in this study did not report high shame about mental health problems. This may imply that because mental health shame has been highlighted in the UK construction industry, some groups of construction workers already have good awareness of mental health problems: a recent study reported a low level of self-stigma in male Australian construction workers (Milner et al, 2017). Though not substantial, as many as 15% of participants in this study had mental health training, and 14% received mental health support.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Contrary to our hypothesis and previous findings (Alderson, 2017), construction workers in this study did not report high shame about mental health problems. This may imply that because mental health shame has been highlighted in the UK construction industry, some groups of construction workers already have good awareness of mental health problems: a recent study reported a low level of self-stigma in male Australian construction workers (Milner et al, 2017). Though not substantial, as many as 15% of participants in this study had mental health training, and 14% received mental health support.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, as many construction workers work at diverse sites, the accessible nature of online training may be suited to this group of workers. Research into this type of intervention would need to be careful of information sharing between the intervention and passive control groups, as that could reduce mental health shame in the control group (Milner et al, 2017). There were some limitations to this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Perceptions and beliefs about suicide are known to inhibit help-seeking [ 10 ]. Self-stigma (self-blame, shame) is known to reduce help-seeking among those with mental illness [ 11 , 12 ]. While not immutable, it is known that self-stigma is difficult to shift [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-stigma (self-blame, shame) is known to reduce help-seeking among those with mental illness [ 11 , 12 ]. While not immutable, it is known that self-stigma is difficult to shift [ 12 , 13 ]. There is also evidence that beliefs about treatment effectiveness or non-effectiveness serves to stymie help-seeking, as does a lack of perceived need [ 14 ].…”
Section: Introductionmentioning
confidence: 99%